Pemanfaatan Zotero sebagai Media Pengelolaan Referensi: Pelatihan bagi Mahasiswa Pendidikan Ekonomi - Wahyu Muh. Syata; Muhammad Juwantho Lewa; Murni Nia; Murniati; Muh. Ilham; Ilhamurrahman M Hubaib; Bellona Mardhatillah Sabillah; Jumatin; Hasniah (Jurnal Ragam Pengabdian, 2025)
The ability to write scientific papers that adhere to academic standards is an important skill for students, especially those in the Economics Education Study Program. One of the common challenges faced by students is the proper management of references and citations. To address this issue, a training program was conducted on the use of the Zotero application as reference management software. The service activities were carried out thru lectures, discussions, and hands-on practice, attended by students from the Economics Education program at the Faculty of Teacher Training and Education, Halu Oleo University. The training results show that participants were able to understand the basics of reference management, install and integrate Zotero with Microsoft Word, import references from various sources, and generate automatic citations and bibliographies according to APA style. Although there were some technical constraints, such as difficulty installing the plugin in Word and fixing metadata, these constraints were overcome thru direct guidance. Overall, this training successfully improved students' ability to manage references effectively, efficiently, and in accordance with academic standards.